OPPORTUNITIES FOR FINANCING GREEN INVESTMENTS THROUGH COMMERCIAL BANKS - Khujumov Nurbek Obidjon ugli (Journals Park Publishing, 2025)
In the article Financing green investments through commercial banks is currently one of the most important directions for ensuring sustainable development. This process includes supporting energy efficiency, renewable energy sources, waste recycling, environmentally friendly transport, and the rational use of water resources. Also, the introduction of ESG principles into the investment policy of banks, the application of tax benefits and innovative financial technologies will increase the effectiveness of this process. The research results show that green investments not only open up new opportunities for the banking system, but also play an important role in ensuring economic stability and environmental security.
Keywords: Green investments, commercial banks, green loans, green bonds, ESG principles, sustainable development, environmental projects, renewable energy, financial innovations, public-private partnership.